Operational Risk Management pada PT Kimia Farma Sungwun Pharmacopia - Achyar, Nadia Nurvita Ilahi; Hartoyo, Hartoyo; Palupiningrum, Agustina Widi; Ilmi, Sendy Watazawwadu (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2024)
Purpose Operational risk management is an important part of ensuring the sustainability of a company, especially in the pharmaceutical industry that faces various complex challenges. This study aims to identify operational risks, map risks, and design risk treatments at PT Kimia Farma Sungwun Pharmacopia (KFSP) based on the ISO 31000:2018 framework. Methodology The research method used is descriptive qualitative with a data triangulation approach through interviews and surveys using questionnaires. Findings The results showed that there were 17 operational risks identified, consisting of 3 extreme risks, 4 high risks, 6 medium risks, and 4 low risks. Risk analysis focused on the level of likelihood and impact, which were then mapped into a risk matrix to determine mitigation priorities. Suggestion The discussion showed that extreme and high category risks, such as delays in customer receivables and product quality discrepancies, require priority mitigation actions through efforts to maintain the continuity of the company's operations